CD24 Ala57Val polymorphism predicts pathologic complete response to sequential anthracycline- and taxane-based neoadjuvant chemotherapy for primary breast cancer - Marmé, Frederik; Werft, Wiebke; Keller, Sascha; Wang, Xiaoli; Benner, Axel; Burwinkel, Barbara; Sinn, Peter; Fastner, Sarah; Sohn, Christof; Moldenhauer, Gerhard; Rupp, Christian; Rupp, Anne-Kathleen; et al. (Breast cancer research and treatment, 2012)
Overexpression of CD24 is an independent prognostic factor for breast cancer. Recently, two polymorphisms in the CD24 gene were linked to disease risk and progression in autoimmune diseases. Here, we evaluated the clinical relevance of these polymorphisms with respect to their potential to predict a pathologic complete response (pCR) to neoadjuvant chemotherapy (NCT) for primary breast cancer (PBC), one of the strongest prognostic factors in this setting. A total of 257 patients were randomized to either doxorubicin/cyclophosphamide (AC) or doxorubicin/pemetrexed (AP), both followed by docetaxel (Doc) as NCT for T2-4 N0-2 M0 PBC as part of an international, multicenter, randomized phase II trial. CD24 polymorphisms were analyzed on germ line DNA and correlated with clinicopathologic variables and pCR. No significant associations were found between either of the polymorphisms and any of the clinicopathologic variables. In a multivariate analysis, CD24 Val/Val genotype was the only significant predictor of pCR (OR: 4.97; P = 0.003). The predictive potential was significant in both treatment arms and in the hormone receptor-positive subgroup. There was no correlation between CD24 3′UTR (TG/Del) genotype and pCR. We did not observe any association between CD24 genotype and CD24 protein expression or in vitro chemosensitivity, but there was a significant correlation between CD24 Val/Val and intratumoral lymphocyte aggregates. In conclusion, CD24 Ala/Val SNP is a strong and independent predictor of pCR after NCT for PBC and may affect immune functions rather than tumor characteristics. Further evaluation of the CD24 function and validation of its predictive potential are clearly warranted.